EVALUATING PORTFOLIO PERFORMANCE OF COMPANIES’STOCK LISTED IN LQ45 BASED ON SHARPE, TREYNOR AND JENSEN METHOD - Zakarias, Vernando A; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2015)
Capital market activity has an important role in developing the national economy, in order to enter the financial market, the investor needs to know about the risk in the capital market itself and determine the best stock to be taken. There are three common methods of analysis such as Sharpe ratio, Trenor ratio and Jensen’s alpha which are sometimes confuse the investor in order to take which one of these three is the better method. This research objective is to identify whether there is a difference of portfolio performance among these three methods on LQ 45 by analyzing the performance of each sampling stock from LQ 45. This research was using Z-score standardized to standardized these three method and after that used one-way ANOVA to find whether there is any difference among these three methods or not. Conclusion this research showed no difference between any of these three methods. Any of this method can be used by the investor to analyze the ratio of portfolio performance. As a recommendation, using these three methods simultaneously can provide better information for manager as part of investment management process. Keywords: portfolio performance, z-score, sharpe ratio, treynor ratio, jensen’s alpha